#39 : Identification of Pharmacologically Active Small Molecules that Induce Spheroid Attachment and Embryo Implantation In Vitro and In Vivo - Truong Thai Ha Nguyen; Bao G Huynh; Duy L Nguyen; Thuy TH Dao; Tuong M Ho (Fertility & Reproduction, 2023)
Background and Aims: Human endometrium is receptive to embryo implantation during the mid-secretory phase of the menstrual cycle. The in vitro spheroid-endometrial epithelial cells co-culture model was used in this study. We hypothesized that the small molecules from thelibrary of pharmacologically active compounds (LOPAC) can effectively enhance embryo implantation. Method: We established a high-throughput in-vitro spheroid-endometrial epithelial (BeWo-Ishikawa) cells coculture model to screen 1280 LOPAC. The top 20 small molecules which increased spheroid attachment rate were further studied in the non-receptive cell lines (HEC-1B and AN3CA). Endometrial cells were either treated with 1% DMSO (vehicle control), AZA at 20 μM (positive control) or LOPAC at 10 μM for 48 h. The trophoblastic BeWo spheroids were generated by AggreWell and the number of attached spheroids after coculture were counted. The effect on mice was studied by trans-cervical injection of LOPAC on 1.5-day postcoital (dpc) and the number of implantation sites on 5.5 dpc were evaluated. Results: Screening of 1280 LOPAC identified 255 molecules increased, and 173 molecules significantly decreased the spheroid attachment rate. The top 20 potential molecules were further studied and three of them were found to significantly increase spheroid attachment in the HEC-1B cells. Another molecule J was found to suppress spheroid attachment in receptive Ishikawa and RL95-2 cells while increase spheroid attachment significantly in non-receptive HEC-1B and AN3CA cells. In mice, molecule J could significantly increase the number of implantation sites on the treated sides when compared with non-treated sides. Conclusion: Three molecules were found to increase spheroid attachment in receptive Ishikawa cells and non-receptive HEC-1B cells. Another molecule J can increase the spheroid attachment in non-receptive HEC-1B and AN3CA cells and increase embryo implantation in ICR mice. [This study is partially supported by the GRF grants 15162211 and 17120720 to KFL]